2017
DOI: 10.1002/hon.2380
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors and outcomes for ibrutinib therapy in relapsed/refractory mantle cell lymphoma—a “real world” study

Abstract: Ibrutinib has demonstrated significant activity in relapsed/refractory mantle cell lymphoma (MCL) in clinical trials. However, the impact of hematopoietic cell transplantation on the outcomes of ibrutinib and the predictive factors for ibrutinib response has not been well studied. Hence, we conducted a multicenter retrospective study of MCL patients who received ibrutinib to (1) determine the overall response rate (ORR), duration of response (DOR), progression-free survival (PFS), and overall survival (OS) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 21 publications
7
65
1
Order By: Relevance
“…Whilst guidelines are available in the UK for first line therapy, there is no agreed standard of care for the management of patients with relapsed/refractory (RR) MCL (McKay et al , ; Zaja et al , ; Atilla et al , ; Dreyling et al , ; Martin et al , ; National Comprehensive Cancer Network, ); options including additional immunochemotherapy, or treatment with novel targeted agents, such as ibrutinib (Dreyling et al , ; Wang et al , ; Martin et al , ). In this context, while real‐world data has linked recent changes in first‐line management to improvements in survival for the Nordic countries and parts of France (Abrahamsson et al , , ; Leux et al , ), as well as for RR MCL in Belgium(Epperla et al , ), comparable data from other countries are exceedingly sparse. Such data are, however, required in order to monitor the impact of therapeutic change at the population level, and to inform decision‐making for clinicians and regulatory agencies.…”
mentioning
confidence: 99%
“…Whilst guidelines are available in the UK for first line therapy, there is no agreed standard of care for the management of patients with relapsed/refractory (RR) MCL (McKay et al , ; Zaja et al , ; Atilla et al , ; Dreyling et al , ; Martin et al , ; National Comprehensive Cancer Network, ); options including additional immunochemotherapy, or treatment with novel targeted agents, such as ibrutinib (Dreyling et al , ; Wang et al , ; Martin et al , ). In this context, while real‐world data has linked recent changes in first‐line management to improvements in survival for the Nordic countries and parts of France (Abrahamsson et al , , ; Leux et al , ), as well as for RR MCL in Belgium(Epperla et al , ), comparable data from other countries are exceedingly sparse. Such data are, however, required in order to monitor the impact of therapeutic change at the population level, and to inform decision‐making for clinicians and regulatory agencies.…”
mentioning
confidence: 99%
“…Epperla et al () reported an ORR of 65%, a median duration of response of 17 months, and a median OS of 22 months. Post‐ibrutinib therapy included a variety of regimens in this cohort (Table ).…”
Section: Clinical Evidence For Ibrutinib Resistance In MCLmentioning
confidence: 98%
“…Multivariate analysis of OS, taking into account the MCL International Prognostic Index (MIPI) and the type of subsequent therapy, did not show statistically significant predictive factors, from the start of the post-ibrutinib therapy (Martin et al, 2016). Epperla et al (2017) reported an ORR of 65%, a median duration of response of 17 months, and a median OS of 22 months. Post-ibrutinib therapy included a variety of regimens in this cohort (Table II).…”
Section: Ibrutinib Treatment Of MCLmentioning
confidence: 99%
See 2 more Smart Citations